Estimates of effective reproduction number of SARS‐CoV‐2 in Brazil using phylodynamic analysis - Silva, Raimundo da (2020)
The estimation of epidemiological parameters (e.g., R0) is an important aspect to mitigate the effects of infectious diseases. With the development of phylodynamic approaches, now it’s possible estimating of epidemiological parameters directly from phylogenetic trees. Here, phylodynamic approaches are used to infer epidemiological parameters from Brazilian SARS-CoV-2 genomes. This study reports a decrease in Re to 1.17 (occurred around mid-March). Re = 1.17 is a value similar to previous reports of R using classical epidemiological approaches and shows evidence of the growth of SARS-CoV-2 in Brazil.